Soil microplastic pollution in China: Current insights and future perspective - ZHANG Yan; DOU Ming; HAO Songze; LI Ping; WANG Guohao; ZHOU Yuze; LIANG Zhijie (Guan'gai paishui xuebao)
【Objective】 Microplastics have emerged as a significant contaminant over the past few decades in various ecosystems. While their presence and impacts in other ecosystems have been well documented, their occurrence in soils and potential implications for environmental and ecological functions, as well as food security, remain poorly understood. This paper reviews the occurrence of microplastics in farmlands in China. 【Method】 The review is based on publications indexed by the Web of Science and CNKI databases. The search results were analyzed using the VOSviewer software, and the microplastics studied in these papers were characterized by their types, abundance, particle diameter, color, and geometric shapes. 【Result】 The types of microplastics found in farmland soils in China show both similarities and regional variations. Polyethylene and polypropylene, mainly from agricultural use and plastic waste, are the dominant microplastics found across most provinces. Microplastics are most abundant in farmland soils in Inner Mongolia, Xinjiang, Shandong, and Guangxi, with their content exceeding 10 000 particles per kilogram of soil. The diameter of microplastic particles primarily ranges from 0 to 2 mm but varies regionally. For example, in Xinjiang and Guizhou, approximately 85% of microplastic particles have a diameter in the range of 0-0.5 mm and 0-0.1 mm, respectively. Common microplastic colors include transparent, white, black, blue, and yellow, with predominant shapes being fibrous, film, fragment, and foam. Based on these findings, this study proposes strategies for mitigating soil microplastic pollution. 【Conclusion】 This review provides valuable insights into the occurrence and characteristics of microplastic pollution in farmland soils in China. These findings provide guidance for developing policies and practices to prevent and control soil microplastic pollution to ensure sustainability of agricultural production and environmental health.